Improving mental health and daytime function in adult insomnia patients predict cognitive behavioral therapy for insomnia effectiveness: A case-control study - Jung-Won Shin; Seonyeop Kim; Bomi Park; Yoon Jung Shin; Sunyoung Park (Sleep Medicine: X, 2023)
Objective: This study investigated demographic, sleep related symptoms and mental health status as predictors of clinically significant treatment responses to cognitive behavioral therapy in adults who have good adherence for the cognitive behavioral therapy for insomnia (CBT-I) program in primary insomnia. Methods: A total of 42 adults with primary insomnia disorder were treated with CBT-I at a university hospital from June 2020 to January 2021. Demographic variables were surveyed and sleep-related symptoms were measured using self-reported questionnaires before and after the intervention, comprising a 6-week interval. The treatment responder group was defined as patients with an Insomnia Severity Index change score >7 compared to baseline. Logistic regression and paired t-test examined whether these factors predicted treatment outcomes for CBT-I. Results: Demographic variables did not predict treatment outcomes. Higher levels of anxiety were associated with a higher likelihood of treatment response (odds ratio [OR] = 1.234; confidence interval [CI]: 1.008–1.511). More severe insomnia at baseline was associated with a greater likelihood of treatment response (OR = 1.450; CI: 1.121–1.875). The lesser the dysfunctional beliefs and attitudes about sleep, the more effective the treatment response (OR = 0.943; CI: 0.904–0.984). Unlike the group of treatment responders, daytime function, depressive mood, and anxiety status did not improve in the group of treatment non-responders after CBT-I intervention. Conclusions: Patients with severe insomnia and anxiety at baseline should be treated more aggressively with CBT-I. During treatment, patients’ mental health problems and daytime activities should be continuously monitored, in order to help improve these problems which might strengthen the effectiveness of CBT-I.